2020
DOI: 10.22382/wfs-2020-002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water soaking-drying cycles on thermally modified spruce wood-plastic composites

Abstract: The overall aim of this work was to gain more insight on the potential of modified wood (TMW) components for use in wood-thermoplastic composites (WPCs). Laboratory-scale TMWPCs were produced, and the effects of severe water soaking-drying cycles on the samples were studied. Water sorption behavior and resulting dimensional and micromorphological changes were also studied, and the results were compared with those of unmodified wood-plastic composites (UWPCs) used as control. The TMW was prepared by cutting a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…It is further difficult to determine whether the polymer has filled the lumena or wood cavities in the wood cell fragments or not, which is usually the case for extruded WPCs. 15,41 However, unfilled lumens did exist (Figure 8). Nevertheless, as mentioned above, the consolidation was high in the sheets, and wood cavities were thus mostly filled or tightly covered with polymer.…”
Section: Micromorphologymentioning
confidence: 99%
See 3 more Smart Citations
“…It is further difficult to determine whether the polymer has filled the lumena or wood cavities in the wood cell fragments or not, which is usually the case for extruded WPCs. 15,41 However, unfilled lumens did exist (Figure 8). Nevertheless, as mentioned above, the consolidation was high in the sheets, and wood cavities were thus mostly filled or tightly covered with polymer.…”
Section: Micromorphologymentioning
confidence: 99%
“…It should be noted that a development of pores has previously been observed for WPC exposed to cycles of water soaking and drying. 15…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the WPC was mixed with 5 wt% nanoparticles, the particles could aggregate on the composite substrate, causing a significant decrease in strength. Kallbom et al (2020) used modified wood to prepare thermoplastic composites and analyzed the water migration behavior of the samples, as well as the resulting changes in macro-size and micro-morphology, through a water soaking-drying cycle measurement. The results showed that the water absorption rate of the modified wood-thermoplastic composite decreased considerably.…”
Section: Introductionmentioning
confidence: 99%